Reversible nanoporous sensors of carbon monoxide in atmosphere - Novikov, Alexander (Discoveries in Agriculture and Food Sciences, 2015)
Optical сhemical compositions being sensitive to carbon monoxide in atmosphere were investigated and tested. The gas sensitive Palladium(II) complexes were immobilized within nano-scale through-out porous glass substrates. Fabricated specimens have demonstrated reversible color changes while interaction with gaseous carbon monoxide in atmosphere.